BRIDGING THE INTENTION-BEHAVIOR GAP IN GREEN CONSUMER BEHAVIOR : TOWARD AN INTEGRATIVE FRAMEWORK - Annisa Wahyuni Arsyad; Lucky Brando Punu; Eirene Copalcanty Tuko; Rahmawati Rahmawati; Syarifah Hudayah (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
Objectives: This study seeks to analyze the factors and underlying mechanisms that influence green consumer behavior, while pinpointing significant conceptual deficiencies in the current literature. The emphasis is on sustainable consumption, highlighting the interaction among psychological, social, and contextual factors that influence consumer behavior. Methodology: A systematic literature review methodology was implemented, employing Publish or Perish (PoP), VOSviewer (VV), and the PRISMA 2020 framework to provide a transparent and organized selection process. A literature search utilizing keywords including green consumer behavior, green buying behavior, green purchase intention, sustainable consumption, and pro-environmental behavior yielded 200 articles from the Scopus database via PoP. The dataset was examined with VOSviewer to delineate research structures and patterns, and then underwent PRISMA screening, resulting in 25 pertinent empirical investigations. Findings: The results demonstrate that human characteristics, psychological mechanisms, and contextual conditions are strongly interconnected in influencing green consumer behavior; however, their integration remains inadequate in existing research. Suggestion: This study fills this gap by presenting an integrated conceptual framework that provides a more thorough, contextually relevant understanding of green consumer behavior.